Business Success of Asnāf Women’s Entrepreneur: an Islamic Law Perspective - Moch. Khoirul Anwar; Ridlwan, Ahmad Ajib; Yan Putra Timur; Citra Dewi , Tazkiyah Nur Laili; Juliana, Juliana; Anwar Adem Shikur (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
Indonesian Muslim communities still have different perceptions towards entrepreneurial activities carried out by women, especially those classified as asnāf or zakat recipients. In fact, some asnāf women can show their existence in the business sector. Therefore, this study aims to describe things in common for successful business women, the role of ʿāmil az-zakāh among the success of the business as well as the Islamic law perspective on working women. As a field study, this study used a qualitative approach. Data was collected through in-depth interviews with six women entrepreneurs who live in Surabaya and three staff of ʿāmil az-zakāh institutions which formerly empowered the entrepreneurs through their programs. The observation was conducted at the informant's business space from September to October 2022. The results of this study indicate that the informants have things in common in running the business, namely high motivation and religiosity. Mustahiq empowerment program and assistance from ʿāmil az-zakāh institutions, meanwhile, encourage them externally. Islamic law grants women the same privileges as men when it comes to employment and economic dealings, provided that they continue to carry out their responsibilities as wives and mothers to their families, among other things. Furthermore, according to some ulemas, a woman may engage in business as long as the revenues are used to address the primary rather than secondary needs.